2018
DOI: 10.1093/mmy/myy133
|View full text |Cite
|
Sign up to set email alerts
|

Yeast-like filamentous fungi: Molecular identification and in vitro susceptibility study

Abstract: Yeast-like filamentous fungi, collected in Italy from 1985 to 2018, were submitted to molecular identification and antifungal susceptibility testings. Clinical isolates were identified as Magnusiomyces capitatus (28), M. clavatus (18), and Geotrichum candidum (2). M. clavatus was prevalent among blood isolates (18/24), M. capitatus among isolates from other biological materials. The intrinsic echinocandin resistance was confirmed. Both species had low minimum inhibitory concentrations (MICs) of itraconazole, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 12 publications
2
21
4
Order By: Relevance
“…S. clavata is almost exclusively confined to systemic, life-threatening infections while the clinical presentation of infections caused by other arthroconidial fungi range from superficial ( Trichosporon spp. ), mucosal ( Galactomyces candidus ), allergic ( Trichosporon pneumonitis) to systemic forms ( T. asahii, M. capitatus , and G. candidus ) (Girmenia et al, 2005; Henrich et al, 2009; Bonifaz et al, 2010; Vaux et al, 2014; de Almeida Júnior and Hennequin, 2016; Durán Graeff et al, 2017; Esposto et al, 2018; Leoni et al, 2018; Salgüero Fernández et al, 2018). AML is the leading underlying condition for systemic infections caused by S. clavata such as for other arthroconidial yeasts (Girmenia et al, 2005; Henrich et al, 2009; Camus et al, 2014; de Almeida Júnior and Hennequin, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S. clavata is almost exclusively confined to systemic, life-threatening infections while the clinical presentation of infections caused by other arthroconidial fungi range from superficial ( Trichosporon spp. ), mucosal ( Galactomyces candidus ), allergic ( Trichosporon pneumonitis) to systemic forms ( T. asahii, M. capitatus , and G. candidus ) (Girmenia et al, 2005; Henrich et al, 2009; Bonifaz et al, 2010; Vaux et al, 2014; de Almeida Júnior and Hennequin, 2016; Durán Graeff et al, 2017; Esposto et al, 2018; Leoni et al, 2018; Salgüero Fernández et al, 2018). AML is the leading underlying condition for systemic infections caused by S. clavata such as for other arthroconidial yeasts (Girmenia et al, 2005; Henrich et al, 2009; Camus et al, 2014; de Almeida Júnior and Hennequin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…That can suggest influence of some unknown epidemiological factor(s). All arthroconidial fungi are ubiquitous in nature but Trichosporon infections are more frequently described in the United States, while M. capitatus prevails in the Mediterranean area (Italy, France, Spain, Turkey, Greece, Tunisia, Israel, Libya, FungiScope ® ) (Schiemann et al, 1998; Gadea et al, 2004; Christakis et al, 2005; Girmenia et al, 2005; García-Ruiz et al, 2013; Vaux et al, 2014; Trabelsi et al, 2015; Del Principe et al, 2016; Durán Graeff et al, 2017; Esposto et al, 2018; Leoni et al, 2018; Salgüero Fernández et al, 2018). We found no correlation between temperature in the Czechia and in Eastern Bohemia and the number of isolated S. clavata strains during the follow-up period (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first case of Geotrichum infection was reported in 1965, and to date other cases or small outbreaks have been described, predominantly in Italy and France (Gadea et al, 2004;Girmenia et al, 2005;Del Principe et al, 2016;Esposto et al, 2018;Stanzani et al, 2019). Clinical presentations were sepsis, pulmonary hepatic and splenic lesions, brain abscesses, and were characterized by a high mortality rate, due to peculiar antifungal resistance patterns, difficult identification and, consequently, delay in diagnosis and correct treatment (Gadea et al, 2004;Cuenca-Estrella et al, 2011;Esposto et al, 2018). A 20-year observational multicenter Italian study reported 35 cases of G. capitatum infection, with a mortality rate of 57.1% (Girmenia et al, 2005;Esposto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical presentations were sepsis, pulmonary hepatic and splenic lesions, brain abscesses, and were characterized by a high mortality rate, due to peculiar antifungal resistance patterns, difficult identification and, consequently, delay in diagnosis and correct treatment (Gadea et al, 2004;Cuenca-Estrella et al, 2011;Esposto et al, 2018). A 20-year observational multicenter Italian study reported 35 cases of G. capitatum infection, with a mortality rate of 57.1% (Girmenia et al, 2005;Esposto et al, 2018). Most of those cases occurred in patients with hematology malignancies, especially during profound neutropenia due to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%